2019
DOI: 10.1002/aet2.10335
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Acute Stress Among Novice Airway Managers

Abstract: Background: The nature of medical emergencies places emergency physicians at risk for high levels of acute psychological stress (APS). Stress-modifying techniques like visualization, breath control, and mental practice may help mitigate APS, but objective markers of stress are difficult to measure in the clinical setting. We explored the relationship between heart rate variability (HRV), a real-time measure of autonomic arousal, and self-reported APS among emergency medicine (EM) residents learning to intubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Mefford and colleagues recently demonstrated that EM residents experience an acute stress response while intubating patients in the operating room. 14 Additionally, EM trainees experience a physiologic stress response while performing medical resuscitations in a simulation environment and while caring for critically ill patients in the emergency department. 7 12 , 15 Although these studies offer vital insight into resident stress, the intensive care unit, operating room, and simulation environment are far different clinical settings than that of an emergency physician in the ED setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mefford and colleagues recently demonstrated that EM residents experience an acute stress response while intubating patients in the operating room. 14 Additionally, EM trainees experience a physiologic stress response while performing medical resuscitations in a simulation environment and while caring for critically ill patients in the emergency department. 7 12 , 15 Although these studies offer vital insight into resident stress, the intensive care unit, operating room, and simulation environment are far different clinical settings than that of an emergency physician in the ED setting.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Surgical, critical care, and medicine trainees experience stress as identified by a variety of subjective and physiologic measures while working clinically; however, few studies have assessed EM resident physician acute stress outside of the simulation environment. 9 14 Mefford and associates demonstrated that EM residents experience a stress response while intubating patients in the operating room during an anesthesiology rotation; however, this is clinical environment is dissimilar to the emergency department. 14 Additionally, while it has been recently demonstrated that EM residents experience an acute stress response while caring for critically ill patients, this patient population accounts for only a subset of ED patient volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has demonstrated correlations between the STAI-6 and HR and cortisol levels as well as a correlation between the STAI-6 and HRV during intubation attempts. 25 , 26 Mefford et al also used HRV as an outcome measure in the evaluation of stress-modifying interventions and demonstrated that HRV may serve as an index of autonomic arousal. 26 Similarly, Kim et al concluded that neurobiologic evidence suggests that HRV can be used as an objective measure of psychological stress.…”
Section: Methodsmentioning
confidence: 99%
“… 25 , 26 Mefford et al also used HRV as an outcome measure in the evaluation of stress-modifying interventions and demonstrated that HRV may serve as an index of autonomic arousal. 26 Similarly, Kim et al concluded that neurobiologic evidence suggests that HRV can be used as an objective measure of psychological stress. 27 Pre-simulation physiologic parameters of HR and HRV were measured for a duration of five minutes using the Elite HRV application (Elite HRV, Asheville, NC) installed on the iPod Touch, 7 th generation (Apple Inc., Cupertino, CA).…”
Section: Methodsmentioning
confidence: 99%